DOZ047.87: Longitudinal evaluation of lung function in infants with esophageal atresia. (24th June 2019) - Landolfo, F; Conforti, A; Columbo, C; Calzolari, F; Savignoni, F; Scuglia, M; Braguglia, A; Dotta, A; Bagolan, P
Abstract: Introduction: Patients affected by esophageal atresia (EA) often faced airway problems, due to multifactorial dynamics (tracheomalacia, gastroesophageal reflex disorder, etc.). The aim of this study was to longitudinally evaluate the lung function test (LFT) in those infants to explore how the LFT modifies at mid-term follow-up. Methods: Retrospective evaluation of lung functions in infants treated for EA (2010–2017) was performed at three time points: 6 months, 12 months, and 24 months. Tidal volume (Vt), respiratory rate (RR), and time to peak tidal expiratory flow as a percentage of total expiratory time (tPTEF/te) were analyzed. ANOVA test was used as appropriate. Results: During the study period 172 patients were treated for EA. Of those 50 infants (28%) underwent LFT at 6 months, 30 at 12 months, and 11 at 24 months. Tracheomalacia was present in 20 infants (42%). Both Vt (6, 79 ml/kg vs 7, 82 ml/kg vs 8, 37 ml/kg— p  = 0, 001) and RR (49, 7 a/min vs 40, 6 a/min vs 34, 0 a/min— p  = 0, 020) significantly improved, while there was no significant difference for tPTEF/te (0, 25 vs 0, 26 vs 0, 29— p  = 0, 62) despite the data showing an improvement trend. Conclusion: The preliminary data suggest that, although EA patients may present impaired LTF in early infancy, lung function seems to improve over time, showing normal pulmonary function test at 24 months. The presence of selection bias and the retrospective nature of the study limit our result. Nonetheless, evaluation of lung function is warranted in EA infants to early detect respiratory symptoms, ideally reducing the impact on short- and long-term pulmonary outcomes.